2012
DOI: 10.1128/jb.00227-12
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the ERES Pathogenicity Region Regulator Ralp3 on Streptococcus pyogenes Serotype M49 Virulence Factor Expression

Abstract: Streptococcus pyogenes (group A streptococcus [GAS]) is a highly virulent Gram-positive bacterium. For successful infection, GAS expresses many virulence factors, which are clustered together with transcriptional regulators in distinct genomic regions. Ralp3 is a central regulator of the ERES region. In this study, we investigated the role of Ralp3 in GAS M49 pathogenesis. The inactivation of Ralp3 resulted in reduced attachment to and internalization into human keratinocytes. The ⌬ralp3 mutant failed to survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 45 publications
(70 reference statements)
0
24
1
Order By: Relevance
“…In contrast, Siemens et al identified only 21 carbon sources with Biolog that supported the metabolism (defined as Ն10% of metabolism on glucose) of the M49 GAS "generalist" strain 591, a strain that is able to colonize both the throat and skin (48). Out of these 21 carbon sources, all but 5 (Tween 40, Tween 80, pectin, mannan, and gelatin) were in common with our studies in M1T1 (Table 3).…”
Section: Discussioncontrasting
confidence: 34%
“…In contrast, Siemens et al identified only 21 carbon sources with Biolog that supported the metabolism (defined as Ն10% of metabolism on glucose) of the M49 GAS "generalist" strain 591, a strain that is able to colonize both the throat and skin (48). Out of these 21 carbon sources, all but 5 (Tween 40, Tween 80, pectin, mannan, and gelatin) were in common with our studies in M1T1 (Table 3).…”
Section: Discussioncontrasting
confidence: 34%
“…Interestingly, the antiphagocytic hyaluronic acid capsule (hasA operon) was also found in our screen, but only in donor A (see Table S2 in the supplemental material). We identified the standalone regulator RofA-like protein 3 (ralp3, Spy0559), which was recently shown to have a role in GAS survival in human blood and plasma (39). The gene perR (Spy0161) encoding the peroxide resistance regulator was found conserved in all donor bloods and has been shown to be important for GAS fitness within the host and necessary for resistance to phagocytic killing in human blood (32).…”
Section: Discussionmentioning
confidence: 99%
“…Since the regulatory network of GAS M49 was published, it is known that Ralp3 regulates genes with metabolic function, especially both lac and fru operons [17]. To compare the ability of different serotypes to utilize sugars, growth experiments in CDM batch cultures with lactose and fructose as sole carbon source were performed.…”
Section: Resultsmentioning
confidence: 99%
“…The GAS serotype M1 genome sequence [23] revealed the existence of two additional Ralp regulators, Ralp3 and Ralp4 [24]. Both were partially characterized [14], [17], [25]. Kreikemeyer and colleagues exclusively found ralp3 homologues genes in the genomes of GAS serotypes M1, M4, M12, M28, and M49 [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation